Pupuk Organik Cair dari Akar Pisang dengan Penambahan Urine Sapi Sebagai Katalis - Muttaqin, Anfai Syifa; Sani, Sani (LPPM Universitas Internasional Batam, 2024)
Kalipucang Village is included in Tutur District, Pasuruan Regency. One of the commodities is beef and processed bananas. A lot of banana roots and cow urine are thrown away because they are waste products from agriculture and livestock. Efforts to reduce waste by processing the waste into liquid organic fertilizer. This innovation program was carried out using bran, shrimp paste, brown sugar, whiting, molasses and cow urine. The results showed that liquid organic fertilizer had a brownish color with a level of dilution and an unpleasant aroma. It can be concluded that the community has been greatly helped by the innovations carried out in Kalipucang Village to reduce agricultural and livestock waste to make it more useful